Dynamic performance evaluation of ballastless track in high-speed railways under subgrade differential settlement. (March 2022) - Jiang, Hongguang; Li, Yixin; Wang, Yujie; Yao, Kai; Yao, Zhanyong; Xue, Zhichao; Geng, Xueyu
Highlights: A FEM of ballastless high-speed railway is developed involving subgrade settlement. Influence of subgrade differential settlement on railway status is evaluated. Maximum dynamic responses occur around settlement wavelengths of 10–20 m. Wheel-rail interaction forces are more effective for railway performance evaluation. Abstract: Ballastless tracks are widely used to provide high rail smoothness in high-speed railways. However, the differential settlement inevitably develops in the subgrade soil, which poses a great threat to the track performance and riding quality via the train-rail dynamic interaction. Since the ballastless tracks are extremely difficult to repair during the maintenance window, it is quite necessary to carry out preventive maintenance to keep the track in good conditions. In order to relate the railway performance with the profiles of subgrade differential settlement, a three-dimensional train-ballastless track-subgrade model was developed incorporating 64 combinations of settlement wavelengths and amplitudes at the roadbed surface. The numerical results were first verified with the measured velocity responses at the concrete base in the Beijing-Tianjin high-speed railway. Then the dynamic responses of the train-track system caused by subgrade differential settlement were analyzed, including the dynamic displacement of train wheels and track structure, wheel-rail interaction forces and car body accelerations. Railway performance was further evaluated as track degradation, lower riding comfort and risk of train safety based on these indicators at different settlement profiles. Results show that increasing settlement amplitudes result in stronger dynamic wheel-rail interaction and vibration of car body. However, critical settlement wavelengths of 10 m and 10–20 m are found to exist where the wheel-rail interaction forces and accelerations of the car body reach their peak values, respectively. It also reveals that the current design limits on the subgrade settlement of high-speed railways are infeasible for infrastructure managers to evaluate the railway status or organize the maintenance works. Moreover, the wheel-rail interaction forces are more credible to determine the railway status than the car body acceleration.